Understanding the Link among employee well-being, training, HRM practices, and organizational citizenship behavior among employees of Football Sports in Bahrain - La'aleh Al-Aali (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Sports play a crucial role in enhancing the tourism industry of a country. In this respect, sports-related personnel are indispensable. Determining the impact of HRM, training, and employee well-being on employee engagement and organizational citizenship was the primary objective of this study. This study also evaluated employee commitment's role as a mediator. Data were obtained from Bahraini employees participating in football activities for this purpose. The respondents provided the information by completing questionnaires. The survey was disseminated to Bahraini employees who participated in football athletics. The valid response rate for the investigation was 73.62 percent. The gathered data were analyzed using SEM and the cutting-edge PLS 3.3.9 application. The study's findings indicate that HRM practices, training, and well-being positively affect employee commitment. Additionally, employee commitment positively affects organizational citizenship behavior. However, this research supports the mediating effect of employee dedication. These findings are useful for future academic study and football decision-makers in Bahrain regarding relevant HR policies.